Killstreak [videorecording (DVD)] - Lawrence, Andrew; Cruz, Alberto de la; Romero, RV; Mahone, Austin; Vertes, Kendall; Ramos, Tonio; Ghen, Eliana (Gravitas Ventures, 2024)
A group of streamers discover that the survival horror game Killstreak is haunted. The line between game and reality begins to blur die in the game, and you die in real life. Live on stream, they must survive or face deadly consequences.